2007
DOI: 10.1055/s-2006-924441
|View full text |Cite
|
Sign up to set email alerts
|

Survival Following Complete Resection of Multifocal T4 Node-Negative NSCLC: A Retrospective Study

Abstract: Patients with N0 multifocal intralobar NSCLC should be upstaged but not to stage IIIB. They should undergo complete surgical resection whenever multiple nodules are detected preoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Typically, only one separate tumor nodule was reported; several studies found no difference in OS for one versus two or more nodules, 14,20 but one found a trend toward better OS with solitary nodules (5-year OS of 62% versus 33%, p ¼ 0.18). 21 Several studies found significantly better OS for smaller versus larger primary tumors 11,14,22 or a similar trend. 24 OS in large registries is slightly lower; it is unclear how many of these patients were resected, but it appears that most were.…”
Section: Literature Reviewmentioning
confidence: 88%
“…Typically, only one separate tumor nodule was reported; several studies found no difference in OS for one versus two or more nodules, 14,20 but one found a trend toward better OS with solitary nodules (5-year OS of 62% versus 33%, p ¼ 0.18). 21 Several studies found significantly better OS for smaller versus larger primary tumors 11,14,22 or a similar trend. 24 OS in large registries is slightly lower; it is unclear how many of these patients were resected, but it appears that most were.…”
Section: Literature Reviewmentioning
confidence: 88%
“…All these considerations support the view that multifocal lung cancers should be staged pT1 (m) or pT2 (m) according to the general recommendations of TNM system rather than p3B or p4 stage, provided that these tumors feature different histopathologic appearance, presence of carcinoma in situ component, absence of lymphatic/vascular channel invasion, or occurrence of different molecular profiles suggestive of independent origin [61,62], as also indicated by the K-ras mutation analysis in our study ( Table 6). The main lesson of these multifocal tumors is that they may have good prognosis following radical surgical excision in comparison with early metastatic pT4 or pM1 lesions, and that a different TNM staging approach should be adopted for pN0 multiple synchronous tumors featuring the above-reported criteria for multifocality [30,31,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a modified system of tumor staging was introduced for differentiating multiple primaries (pT1m or pT2m) from intrapulmonary early metastases (pT4 or pM1) [30][31][32][33][34]. In particular, multiple nodules exhibiting different histopathologic features, an in situ component (BAC for adenocarcinoma), or lack of overt vascular/lymphatic invasion were classified as multiple synchronous tumors [30].…”
Section: Tumor Samplesmentioning
confidence: 99%
“…3,4 Although the diagnosis of lung cancer has been researched intensively in recent years, the 5-year survival rate has not been significantly improved. 5,6 The key cause of high mortality is the metastatic potential of the tumor. 7 Therefore, a better understanding of the mechanisms of tumor cell proliferation is a necessary condition for more effective NSCLC management.…”
Section: Introductionmentioning
confidence: 99%